PENGARUH KERAPATAN TANAMAN TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG HIJAU (Phaseolus radiatus L) DI DISTRIK SEMANGGA, KABUPATEN MERAUKE - Rupang,, Maya Sari; Najib, Nardy Noerman; Djaja, Irba; Sainyakit, Yuliana (MEDIAGRO, 2023)
Green beans (Phaseolus radiatus L.) are one of the food ingredients that grow in tropical environments and can be found almost throughout Indonesia. However, mung bean production in Merauke Regency is suspected to have decreased due to ineffective cultivation methods. So it is necessary to test several plant densities to increase mung bean production in Merauke Regency. This study aims to determine whether plant density affects the growth and production of green beans in Semangga District, carried out from June to September. This research was carried out with experimental methods and used Group Random Design (RAK), with 5 (five) treatments and repeated 3 (three) times with density treatments of 40 cm x 30 cm, 40 cm x 25 cm, 40 cm x 20 cm, 40 cm x 15 cm and 40 cm x 10 cm. The results showed that plant density treatment significantly affected the number of flowers, number of pods, number of seeds per pod, weight of 1000 seeds, sample production, and total production. While plant density treatment has no real effect on the level of 95% confidence in plant height and number of leaves. From the results of this study, J4 treatment (40 cm x 15 cm) provided the best growth and yield of green bean production.